Ovarian Follicle Growth during Lactation Determines the Reproductive Performance of Weaned Sows - Tania P. Lopes (Animals, 2020)
Factors causing variability in ovarian follicle size among weaned sows are not well known. This field study aimed to disclose influencing factors and evaluate if the differences at weaning were established during lactation. Ovaries were scanned using transrectal ultrasound. The first experiment was conducted over a year with 191 randomly chosen sows that were hierarchically grouped (p < 0.001) according to ovarian follicle diameter reached at weaning: Small (0.20–0.30 cm; n = 37), medium (0.31–0.39 cm; n = 75), and large (0.40-1.00 cm; n = 69). Sows with small follicles showed a higher incidence of post-weaning anestrus (p < 0.01), longer wean-to-estrus/ovulation intervals (p < 0.01) and farrowing smaller litters (p < 0.05). Ovaries with small follicles were more common among sows weaned in summer–autumn than in winter–spring (p < 0.01) and among sows of lower parity (1–3) (p < 0.05). In the second experiment, with 40 sows randomly chosen at farrowing, the ovaries were scanned at 7, 14, and 21 d post-partum. Sows showed great variability in ovarian follicular size during lactation with a consistent relationship between the three measurement times (r = 0.84, p < 0.01). Follicle size was smaller in sows nursing in summer–autumn than in winter–spring (p < 0.05). In conclusion, early lactation dictates the great variability in ovarian follicular diameter at weaning shown by sows. Sows with smaller follicles at weaning had longer intervals for estrus and ovulation and smaller litters at farrowing and they were in greater numbers among sows weaned during the summer and fall and among those with fewer previous farrowing.